2011
DOI: 10.1007/s10549-011-1444-z
|View full text |Cite|
|
Sign up to set email alerts
|

Strength training stops bone loss and builds muscle in postmenopausal breast cancer survivors: a randomized, controlled trial

Abstract: Targeted exercise training could reduce risk factors for fracture and obesity-related diseases that increase from breast cancer treatment, but has not been sufficiently tested. We hypothesized that progressive, moderate-intensity resistance + impact training would increase or maintain hip and spine bone mass, lean mass and fat mass and reduce bone turnover compared to controls who participated in a low-intensity, non-weight bearing stretching program. We conducted a randomized, controlled trial in 106 women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
188
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(204 citation statements)
references
References 61 publications
6
188
0
10
Order By: Relevance
“…In cancer survivors, Winters-Stone et al 95 recently reported the results of their randomized controlled trial that examined the effect of a targeted exercise program of resistance training and impact-loading activities on the bone health of women (X50 years) with breast cancer. Following the 12-month intervention, women in the exercise group maintained BMD at the lumbar spine compared with controls (0.47% versus À2.13%).…”
Section: Resistance Training Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer survivors, Winters-Stone et al 95 recently reported the results of their randomized controlled trial that examined the effect of a targeted exercise program of resistance training and impact-loading activities on the bone health of women (X50 years) with breast cancer. Following the 12-month intervention, women in the exercise group maintained BMD at the lumbar spine compared with controls (0.47% versus À2.13%).…”
Section: Resistance Training Programsmentioning
confidence: 99%
“…61,98 High-impact exercise has also been shown in both breast cancer survivors and non-prostate cancer populations to be well tolerated and has the potential to both prevent bone loss and increase bone mass. 87,89,93,95,96 Although high-impact exercises are particularly beneficial, activities involving high peak GRFs are not currently recommended for those with established osteoporosis because of their increased risk for fracture. Further, jumping exercises are currently not advised for those with advanced metastatic bone disease because of the increased fracture risk associated with this stage of disease progression.…”
Section: Safety Aspectsmentioning
confidence: 99%
“…More than 70 controlled trials have examined exercise in breast cancer patients and survivors; however, only seven have examined bone health outcomes [71][72][73][74][75][76][77]. Studies assessing bone health in breast cancer patients have typically included women who are peri-or postmenopausal [71][72][73][74][75][76]78], are at least 6 months post primary chemotherapy or radiation therapy [71,72,[75][76][77] and receiving adjuvant selective estrogen receptor modulators or aromatase inhibitors [71][72][73][74][75][76][77]. Three RCTs showed that exercise may prevent the typical loss of BMD experienced in patients that are not exercising [71,77,78].…”
Section: Exercise and Cancer-related Bone Loss In Women With Breast Cmentioning
confidence: 99%
“…Studies assessing bone health in breast cancer patients have typically included women who are peri-or postmenopausal [71][72][73][74][75][76]78], are at least 6 months post primary chemotherapy or radiation therapy [71,72,[75][76][77] and receiving adjuvant selective estrogen receptor modulators or aromatase inhibitors [71][72][73][74][75][76][77]. Three RCTs showed that exercise may prevent the typical loss of BMD experienced in patients that are not exercising [71,77,78]. Bisphosphonates appear to provide better treatment for CTIBL in breast cancer patients than exercise [74], however exercise plus bisphosphonates appears to be better than bisphosphonates alone [76].…”
Section: Exercise and Cancer-related Bone Loss In Women With Breast Cmentioning
confidence: 99%
See 1 more Smart Citation